Atomic structure of Fe90Sc10 glassy nanoparticles and nanoglasses. (October 2017) - Wang, Chaomin; Guo, Xiaoai; Ivanisenko, Yulia; Goel, Sunkulp; Nirschl, Hermann; Gleiter, Herbert; Hahn, Horst
Abstract: Glassy nanoparticles of a Fe90 Sc10 alloy have been studied using small- and wide-angle X-ray scattering. The results indicate that the surface shells have an electron density that is lower than the electron density in the cores of the glassy nanoparticles. The lower electron density seems to result primarily from a lower atomic packing density of the surface shells rather than from compositional variations due to surface segregation. During the consolidation of the glassy nanoparticles, the short-range order and the extra free volume content present in the shells may be transferred into the interfaces of the resulting bulk Fe90 Sc10 nanoglasses. Graphical abstract: